Implementasi Metode Ahp-Topsis untuk Rekomendasi Penerima Beasiswa: Studi Kasus Universitas Dumai - Melati Rahma Suri (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2025)
Providing scholarships to high-achieving students from underprivileged families is a crucial step in ensuring equal access to higher education. However, subjective selection processes often reduce the effectiveness and fairness of scholarship distribution. The selection process for scholarship recipients often faces challenges in terms of objectivity due to the large number of criteria variables that must be considered.